PENGARUH PERENCANAAN PAJAK, BEBAN PAJAK TANGGUHAN DAN BEBAN PAJAK KINI TERHADAP MANAJEMEN LABA - Aulia, Fitra; Pernamasari, Rieke (Program Studi Akuntansi, Universitas Kuningan, 2025)
This study aims to analyze the effect of tax planning, deferred tax expenses, and current tax expenses on earnings management practices in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 period. The research is grounded in agency theory, which posits that information asymmetry can drive agents to engage in earnings management to achieve personal interests. The study employs a quantitative method with a causal research design. The sample consists of 75 manufacturing companies selected through purposive sampling based on specific criteria, resulting in 225 data observations. The findings reveal that tax planning does not affect earnings management. This is because the primary purpose of tax planning is to minimize tax burdens, which does not align with the goal of earnings management to maintain or increase profits for managerial incentives. Deferred tax expenses negatively affect earnings management, as temporary differences in the calculation of commercial and fiscal profits lead to larger deferred tax expenses, thereby reducing management’s incentive to engage in earnings management. Conversely, current tax expenses do not have a significant impact on earnings management. The size of current tax expenses is more influenced by taxable income, which limits management's ability to manipulate profit figures significantly.